THE PRAGMATIC FUNCTIONS OF INTERNET ABBREVIATIONS IN YOUTH ONLINE COMMUNICATION (SCIENCE TIME JOURNAL, 2026)
This article explores the pragmatic functions of internet abbreviations in youth online communication. With the rapid development of digital technologies and social media platforms, young people increasingly use abbreviations such as LOL, BRB, IMO, and IDK to convey meanings efficiently. The study analyzes how these abbreviations function not only as linguistic shortcuts but also as pragmatic tools expressing emotions, attitudes, social closeness, and group identity. Special attention is given to their role in informal discourse, including chat messages, social networking sites, and online forums. The research demonstrates that internet abbreviations enhance communicative efficiency, reflect pragmatic intent, and contribute to the construction of youth digital discourse.